1998
DOI: 10.1046/j.1526-4610.1998.3804308.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distinctive Headache of the Occipital Condyle Syndrome: A Report of Four Cases

Abstract: Four examples of occipital condyle syndrome, that is, unilateral occipital pain and ipsilateral tongue paralysis due to selective erosion of the occipital condyle, are reported. The four patients complained of a continuous, severe, unilateral, occipital pain which kept them with the head rotated to the side of the pain and held with their hands. The pain became unbearable with head rotation to the nonpainful side and with unilateral suboccipital palpation. The onset of this very characteristic unilateral heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…The commonest association of OCS is with metastases to skull-base and primary head and neck tumors [1][2][3][4][5]. In the largest published series of 100 patients with 12th nerve paresis (Keane et al,), malignancy accounted for 49% cases; whereas trauma, infection, stroke and GBS were responsible for the remaining cases [6].…”
Section: Discussionmentioning
confidence: 99%
“…The commonest association of OCS is with metastases to skull-base and primary head and neck tumors [1][2][3][4][5]. In the largest published series of 100 patients with 12th nerve paresis (Keane et al,), malignancy accounted for 49% cases; whereas trauma, infection, stroke and GBS were responsible for the remaining cases [6].…”
Section: Discussionmentioning
confidence: 99%
“…The occipital condyle syndrome has been associated with metastases to the base of the skull and primary head and neck tumors (Greenberg et al, 1981; Moris et al, 1998; Capobianco et al, 2002). The largest case series ever reported about CN XII palsy indicated that almost half of these cases are due to malignancies (Keane, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[12345] We herein present an extremely rare case of OCS which occurred as the first sign of skull metastasis from lung cancer.…”
mentioning
confidence: 99%
“…[12345] The pain can be successfully controlled with radiotherapy if it is delivered early to the patients with OCS caused by skull metastasis. [13] Only a minority of patients with skull metastasis are candidates for surgical resection; however, in patients without known systemic cancer, a biopsy is useful to establish the diagnosis because OCS is not always secondary to malignant diseases. [25]…”
mentioning
confidence: 99%